International Students, Reflection, and Employability - Ryan, Mary; Barton, Georgina (Journal of International Students, 2020)
The International Student Barometer indicates international students’ interest in work experience, career advice and employment post-study. A necessary skill for all graduates is the ability to be able to reflect on and in professional practice, yet there is limited research that explores reflection, the teaching of reflective thinking, and reflexivity for international students. Our research has shown that international students may approach the process of reflection differently due to their cultural differences so it is important that universities acknowledge and consider further ways in which to teach and assess reflection for international students. This special issue shares 7 papers related to international students and reflection by drawing on Rodgers’ four functions of reflection. We hope that the special issue is of value to the journal’s readership, particularly in regard to assisting both academic and support staff in universities with their work on reflection with international students.